Engineering properties of foods - Rao, M A, Ed; Syed S H Rizvi, Ed; Ashim K Datta, Ed; Jasim Ahmed, Ed (CRC Press, 2014)
"Preface We are pleased to present the fourth edition of Engineering Properties of Foods. During the last few years, food structure/micro-structure has remained a subject of research interest. Furthermore, significant developments have taken place in the area of high-pressure processing (HPP), and the process has been approved by the Food and Drug Administration (FDA) for pasteurization of food. Kinetic data related to HPP play a crucial role for validating the pressure-assisted pasteurization. On the basis of these developments, three new chapters: "Microstructural Properties of Foods," "Glass Transition in Foods," and "Kinetics and Process Design for High-Pressure Processing" have been added in the fourth edition. Most of the existing chapters were revised to include recent developments in each subject. The chapter on colorimetric properties of food was removed from the earlier edition. Data on physical, chemical, and biological properties have been presented in the book to illustrate their relevance and practical importance. We have added Dr. Jasim Ahmed as a coeditor to help with this rather large undertaking. In looking for experts on topics, we have also made an effort to expand the international participation of authors. We have made a special effort to follow a consistent format for the chapters so that readers can follow each chapter easily. Thus, each chapter includes an introduction, property definition, measurement procedure, modeling, representative data compilation, and applications"--